2011
DOI: 10.7863/jum.2011.30.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Analysis of Portal Pressure by Contrast-Enhanced Sonography in Patients With Cirrhosis

Abstract: Objectives Free portal pressure measurement is a reliable method for assessment of portal pressure in patients with cirrhosis. Intrahepatic circulatory time analysis of a sonographic contrast agent can assess liver fibrosis and its severity. The purposes of this pilot study were to assess the correlation between the intrahepatic circulatory time and free portal pressure and to assess whether intrahepatic circulatory time analysis can be used to predict portal venous pressure severity. Methods The intrahepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The HV–HA index had been used in many studies to correct the differences of participants’ blood circulation time [20,21,26]. As expected, the AUROCs of HV–HA was larger than that of HVAT (0.883 vs. 0.838 for assessing presence of EV and 0.915 vs. 0.840 for assessing high-risk EV).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The HV–HA index had been used in many studies to correct the differences of participants’ blood circulation time [20,21,26]. As expected, the AUROCs of HV–HA was larger than that of HVAT (0.883 vs. 0.838 for assessing presence of EV and 0.915 vs. 0.840 for assessing high-risk EV).…”
Section: Discussionmentioning
confidence: 69%
“…PSI was the difference between the peak signal intensity in the liver parenchyma and baseline intensity; moreover, TTP was defined as the time interval between injection and liver parenchyma peak time [18,21]. To lessen the impact of variations in the blood circulation time, HV–HA (HVAT minus HAAT) and PV–HA (PVAT minus HAAT) were calculated [20,21]. The time from 10% to 90% of liver parenchyma peak signal intensity was expressed as the rise time [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interval time between vessels is a representative parameter for microbubble hemodynamics and shows close correlation with portal pressure, between free portal pressure and hepatic vein–hepatic artery interval time (r=−0.804, p=0.009) or the portal vein–hepatic artery interval time (r=0.506, p=0.036) 27. More recent studies have demonstrated original parameters for portal pressure; the first study proposed “regional hepatic perfusion” using SonoVue, which correlated with HVPG (r=0.279, p=0.041) and hyperdynamic syndrome markers 28.…”
Section: Contrast-enhanced Usmentioning
confidence: 99%
“…However, it is sometimes difficult to use conventional measurements to diagnose well-compensated cirrhosis. The behavior of the microbubbles in sonographic contrast medium in the portal vein may reflect hemo dynamic changes due to hepatic fibrosis [1]. In this comparative study, patients were divided into two groups (noncirrhotic and cirrhotic) according to the histological findings of the resected specimens.…”
mentioning
confidence: 99%